(untitled) (The Strategic Review for Southern Africa, 2020)
In 2013, Namibia’s ruling party, the South West Africa People’s Organisation (SWAPO), amended its constitution to implement the 50/50 gender policy. This policy required equal representation of men and women in all its leadership structures and in its representation in institutions such as the National Assembly. The party had been zigzagging on this policy it had adopted at its 2002 congress. Four years since the implementation of SWAPO’s 50/50, an analysis of the impact of this policy in the National Assembly paints a troubling picture. At the level of substance by looking at parliamentary motions tabled, we find that SWAPO’s 50/50 policy in the National Assembly – which resulted in increased number of women in the legislature - did not lead to meaningful agenda setting in favour of women political participation. This article reflects critically on the gender policy in the 6th parliament’s National Assembly, which is the principal law-making and policy-setting arm of parliament with a view to assess whether there have been successes in facilitating women empowerment and participation in a meaningful way.